2009
DOI: 10.1098/rspb.2009.1343
|View full text |Cite
|
Sign up to set email alerts
|

Sauropod dinosaurs evolved moderately sized genomes unrelated to body size

Abstract: Sauropodomorph dinosaurs include the largest land animals to have ever lived, some reaching up to 10 times the mass of an African elephant. Despite their status defining the upper range for body size in land animals, it remains unknown whether sauropodomorphs evolved larger-sized genomes than non-avian theropods, their sister taxon, or whether a relationship exists between genome size and body size in dinosaurs, two questions critical for understanding broad patterns of genome evolution in dinosaurs. Here we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The finding in this study that nonavian dinosaurs possessed genomes as small as those of modern birds directly rejected the hypothesis (83) that flight was initially responsible for driving down genome size in ancestral avian lineages. This study also suggested that the depauperate retroelement landscape of modern birds was likely inherited from their dinosaur (saurischian) ancestors (140,145). Although only gross descriptors of the genome can be analyzed in this way, important insights into the tempo and mode of genome evolution have been made.…”
Section: Paleogenomics and Rates Of Evolutionmentioning
confidence: 89%
“…The finding in this study that nonavian dinosaurs possessed genomes as small as those of modern birds directly rejected the hypothesis (83) that flight was initially responsible for driving down genome size in ancestral avian lineages. This study also suggested that the depauperate retroelement landscape of modern birds was likely inherited from their dinosaur (saurischian) ancestors (140,145). Although only gross descriptors of the genome can be analyzed in this way, important insights into the tempo and mode of genome evolution have been made.…”
Section: Paleogenomics and Rates Of Evolutionmentioning
confidence: 89%
“…It was recently established that incorporating phylogenetic information in this way is far more accurate than nonphylogenetically informed methods [3]. Our data were added to the dataset and phylogeny of Organ et al [4]. Estimated genome sizes for our four taxa were compared with measured C-values from the Animal Genome Size Database [10].…”
Section: Methodsmentioning
confidence: 99%
“…However, one potentially confounding problem has yet to be addressed. Published studies have been inconsistent in their choice of bones for lacunar measurements, and measurements from different types of bone shape (long, irregular, flat) have been included in the same datasets [3][4][5][6]. Previous work has hinted that there may be variation in the size of osteocyte lacunae across the skeleton of an individual [6], and if true, this may compromise the integrity of genome size estimates based on measurements from different types of bone.…”
Section: Introductionmentioning
confidence: 99%
“…A study on megabats found that they exhibit less genome size variation and, often times, smaller genomes than microbats despite having larger body sizes [18]. Indeed, vertebrate-wide studies have not yield evidence for a relationship between genome size and body size [3,19]; this is inconsistent with models proposing population size as the dominant factor in driving genome size evolution [20]. Instead of correlating genome size with metabolic rate, numerous other studies correlate the former with multiple flight efficiency variables, such as flight muscle size, heart index, wing area, and wing loading index.…”
Section: The Effect Of Powered Flight On Genome Sizementioning
confidence: 99%